Inspiratory muscle training improves rowing performance - Volianitis, S.; McConnell, A. K.; Koutedakis, Y.; McNaughton, L.; Backx, K.; Jones, D. A. (Medicine & Science in Sports & Exercise, 2001)
Purpose: To investigate the effects of a period of resistive inspiratory muscle training (IMT) upon rowing performance. Methods: Performance was appraised in 14 female competitive rowers at the commencement and after 11 wk of inspiratory muscle training on a rowing ergometer by using a 6-min all-out effort and a 5000-m trial. IMT consisted of 30 inspiratory efforts twice daily. Each effort required the subject to inspire against a resistance equivalent to 50% peak inspiratory mouth pressure (PImax) by using an inspiratory muscle training device. Seven of the rowers, who formed the placebo group, used the same device but performed 60 breaths once daily with an inspiratory resistance equivalent to 15% PImax. Results: The inspiratory muscle strength of the training group increased by 44 +/- 25 cm H2O (45.3 +/- 29.7%) compared with only 6 +/- 11 cm H2O (5.3 +/- 9.8%) of the placebo group (P < 0.05 within and between groups). The distance covered in the 6-min all-out effort increased by 3.5 +/- 1.2% in the training group compared with 1.6 +/- 1.0% in the placebo group (P < 0.05). The time in the 5000-m trial decreased by 36 +/- 9 s (3.1 +/- 0.8%) in the training group compared with only 11 +/- 8 s (0.9 +/- 0.6%) in the placebo group (P < 0.05). Furthermore, the resistance of the training group to inspiratory muscle fatigue after the 6-min all-out effort was improved from an 11.2 +/- 4.3% deficit in PImax to only 3.0 +/- 1.6% (P < 0.05) pre- and post-intervention, respectively. Conclusions: IMT improves rowing performance on the 6-min all-out effort and the 5000-m trial.